Trajectory of a synthetic jet issuing into high-Reynolds-number turbulent boundary layers. (8th October 2018) - Berk, Tim; Hutchins, Nicholas; Marusic, Ivan; Ganapathisubramani, Bharathram
Abstract : Synthetic jets are zero-net-mass-flux actuators that can be used in a range of flow control applications. For some applications, the scaling of the trajectory of the jet with actuation and cross-flow parameters is important. This scaling is investigated for changes in the friction Reynolds number, changes in the velocity ratio (defined as the ratio between the mean jet blowing velocity and the free-stream velocity) and changes in the actuation frequency of the jet. A distinctive aspect of this study is the high-Reynolds-number turbulent boundary layers (up to $Re_{\unicode[STIX]{x1D70F}}=12\, 800$ ) of the cross-flow. To our knowledge, this is the first study to investigate the effect of the friction Reynolds number of the cross-flow on the trajectory of an (unsteady) jet, as well as the first study to systematically investigate the scaling of the trajectory with actuation frequency. A broad range of parameters is varied (rather than an in-depth investigation of a single parameter) and the results of this study are meant to indicate the relative importance of each parameter rather than the exact influence on the trajectory. Within the range of parameters explored, the critical ones are found to be the velocity ratio as well as a non-dimensional frequency based on the jet actuation frequency, the cross-flow velocity and the jet dimensions. The Reynolds number of the boundary layer is shown to have only a small effect on the trajectory. An expression for the trajectory of the jet is derived from the data, which (in the limit) is consistent with known expressions for the trajectory of a steady jet in a cross-flow.